Survival Analysis of Time to Retest for HIV Among Men Who Have Sex with Men from Metro Manila, Philippines: A Single-Center Prospective Study - Samuel Brando Piamonte; Jhoanne Ynion (San Beda University, 2020)
Background: Regular HIV testing means early detection of the virus and prompt access to treatment. However, factors affecting retesting following receipt of a non-reactive test result are not yet well understood. This study aims to determine the predictors of time to repeat HIV testing among men who have sex with men (MSM) from Metro Manila, Philippines within six months following receipt of a non-reactive test result. Methods: A prospective study was implemented at a community-based HIV testing and counseling center. A total of 250 non-reactive MSM from Metro Manila and with a recent risk of acquiring HIV were the respondents. At baseline, data on socio-demographic factors were gathered; while at follow-up, repeat test status of each participant within six months after baseline was collected. Results: Two retests per 1,000 person-weeks were recorded. Mean survival time was 23.93 weeks, 95% CI: [23.18 - 24.68]. Cox proportional hazards regression demonstrated that statistically significant factors of time to retest were age (HR = 0.90, 95% CI [0.85, 0.96]) and number of tests in lifetime (HR = 1.12, 95%CI [1.06, 1.18]). Conclusion: Although the average time to return is within the recommended period of three to six months, the low return rate suggests the call for encouraging repeat HIV testing among MSM with non-reactive results and recent risk of acquiring HIV. Repeat testing has been shown to be facilitated by age and previous testing history. HIV/AIDS counselors and program administrators can aim for MSM who are older and with relatively low testing history to help meet the global target of ending the HIV/AIDS global epidemic.